PENGARUH TEKNIK OBJEK LANGSUNG TERHADAP KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS VIII SMP NEGERI 11 PADANG - Sari, Desi Atika; Afnita, Afnita; Rasyid, Yulianti (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this study were (1) to describe the skills of wrting the text of the poerty of the students of class VIII SMP Negeri 11 Padang before using direct object technique, (2) to describe the skills of writing the text of the poerty of class VIII students of SMP Negeri 11 Padang after using direct object technique, (3) to analyze the effect of direct object technique on poerty to the writing skills skill of class VIII SMP Negeri 11 Padang. Based on data analysis, the use of writing poerty text of class VIII students of SMP Negeri 11 Padang.. Kata kunci — pengaruh, teknik objek langsung¸ menulis teks puisi